Struktur dan Komposisi Jenis-Jenis Pohon di Taman Nasional Gunung Rinjani bagian Selatan, Lombok, Nusa Tenggara Barat - Mansur, Muhammad (JURNAL BIOLOGI INDONESIA, 2016)
Plant ecology study has been conducted in the southern part of Rinjani Mountain National Park on April 2015 to determinethe structure and composition of tree species. Four plots, 30 x 30 m each were established at four locations, those are; Pal-Belanda (1046 m asl), Pengorot-1 (929 m asl), Pengorot-2 (820 m asl), and Sebau (1134 m asl). The results showed thatthere are two types of forest in the sites, namely the secondary forest (Pal-Belanda, Pengorot-1 and Pengorot-2) and primaryforest (Sebau). From all plots (0.36 ha) we found 36 species of trees (trunk diameter > 5 cm) of 449 individuals, 28 genusand 21 families with a total Basal Area of 16.73 m2 (46.47 m2/ha). Shannon Diversity Index (H) in the Pengorot-2 recorded1,15, followed Pengorot-1 (1.13), Pal-Belanda (1.03) and Sebau (0.72). Saurauia pendula recorded as the dominant speciesin all site with Important Value Species (IVS) of 245% followed Dendrocnide microstigma (IVS = 162%), Platea excelsa(IVS=148.2%), Syzygium glomeruliferum (IVS=72%) and Symplocos cochinchinensis (IVS=49.3%). Myrtaceae andEuphorbiaceae were the common families in the sites. Structure and composition of tree species in the Pal-Belanda,Pengorot-1 and Pengorot-2 were relative similar (Similarity Index 70.3% and 69.4%) but different than in Sebau area(Similarity Index 24.9%).Keywords: Structure, composition, tree diversity, Rinjani, Lombok